Tafsir Tazkiyat al-Nafs Perspektif Sa’îd Ḥawwâ dalam al-Asâs Fî Tafsîr - Saadatul Jannah (Studia Quranika, 2022)
Differences in mufassir backgrounds have an impact on variations in the patterns of sufi interpretation, philosophy, kalam, language and jurisprudence. Al-Asâs Fîr Tafsîr by Sa’îd Ḥawwâ is considered one of the sufism-style interpretations. The claim is based on his devotion to the sufi practice during life which is directly stated in his interpretation of an interpretation. This article aims to explore the thought of Sa'îd Ḥawwâ regarding the theory and practice of Tazkiyat al-Nafs in al-Asâs Fî Tafsîr. This research employs qualitative methods with analysis of text interpretation related to Tazkiyat al-Nafs. The results of this study reveals that the interpretation of the qur'anic text of Sa'îd Ḥawwâ is based on theological tendencies and praxis of his life, this article also proves that the tazkiyah methodology in Sa'îd thought can still be applied for modern society to balance the fatigue of the soul with its various practices.